Analisis Fungsi Kampanye Daring sebagai Sarana Pendidikan dan Gerakan Sosial dalam Menciptakan Kepekaan dan Respon terhadap Kekerasan dalam Rumah Tangga - Lani Dharmasetya; Charles Bronson; Ibnu Mubarok (LPPM Iblam School of Law, 2024)
The current digital age has transformed the way society communicates and interacts, with social media being the primary medium. In this context, Domestic Violence (DV) is a critical issue that has garnered widespread attention, not only in Indonesia but also internationally. This study focuses on how social media, through online campaigns, can enhance awareness and actions against DV. Using a qualitative approach, this research explores the potential of social media as an educational and social mobilization platform to prevent DV. The results indicate that online campaigns have immense potential to engage the community, raise awareness, provide accurate education, support DV survivors, and promote collective action in DV prevention efforts. This study offers new insights into communication strategies in the digital age to address the DV problem.